KAJIAN PERSEPSI PELAKU JASA KONSTRUKSI TENTANG KEGIATAN PENGADAAN JASA KONSTRUKSI - Messah, Yunita A.; Asmat, Maria Y.Y.; Rizal, H. A. (Jurnal Teknik Sipil, 2013)
The The implementation of e-procurement has been used since 2010 in NTT expecially in Kupang and believed could bring up effectively, fairly, efficiently , transparently andakuntability so it is expected to could minimalize the deceitful happened. Therefore it is needed to known if there was the deceitful of construction service conventionally and wich steps in procurement of construction service wich giving chance for deceitful to be happened and could e-procurement could minimalize the deceitful happened on that steps. This research was conducted on service users in Department of public work NTT province and Department of public work in Kupang City and service provider wich has central office and branch office in Kupang city. The technique of data processing and analysis was used Likert Scale. From the result of research could be known that respondent agree there was deceitful on the construction service conventionally with the percentage of the user service is about 77,33%, the contractor is about 81,84% and the consultant is about 78,96%. From the deceitful of conventionall system, it have five step on the construction service conventionall wich often happened is the auction announcement. The input of proposal document the provement of qualification, clarification and negotiation, and winner announcement. From those five steps, three of those were the steps those of auction announcement the input of proposal document and winner announcement could be minimalized the deceitful by e-procurement. While on the step of the provement of qualification, clarification and negotiation it could not minimalized by the e-procurement because there is still happening of the direct meeting in this steps.